A model to predict tribo-dynamic performance of a spur gear pair. (December 2017) - Ouyang, Tiancheng; Huang, Haozhong; Zhang, Ning; Mo, Chunlan; Chen, Nan
Abstract: Noise, vibration and harshness (NVH) as well as scuffing failure are the key design attributes of high-speed gear transmission. Unlike the traditional methods, this study desires to establish a new tribo-dynamic model for spur gear pair to predict the dynamic and tribological behaviors within a wide rang of speeds under various conditions. Therefore, a multiple degrees of freedom discrete dynamic model is combined with an infinite line contact thermal elastohydrodynamic lubrication (EHL) model to investigate the interactive mechanism between the dynamics and tribology, using an iterative calculation program which integrates the Runge-Kutta method and the multigrid method. Serious deviations are found in high speed condition by making a comparison between the quasi-static and tribo-dynamic simulation results, validating the importance of tribo-dynamic model. Numerical results show that the proposed model can provide guidance for engineering practice of high-speed gear design. Graphical abstract: A multiple degrees of freedom discrete dynamic model is combined with an infinite line contact thermal elastohydrodynamic lubrication (EHL) model to investigate the interactive mechanism between the dynamics and tribology, using an iterative calculation program which integrates the Runge-Kutta method and the multigrid method. Highlights: A thermal tribo-dynamic model is proposed by combining a multiple DOF gear dynamic model with a mixed EHL model. Comparisons between the tribo-dynamic and quasi-static conditions are investigate. Variations of tribo-dynamic performance along the line of action are studied at different speeds. The flash temperature rise is discussed within a wide speed range under different conditions.